Penerapan STEAM Project Based Learning “Taman Mini Imun Booster Digital Berbasis QR Code Berbantuan 4DFrame” - Eti Herawati (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2022)
The aim of this study was to improve the learning outcomes students in the material of Cubes and Blocks by implementing the STEAM Project Based Learning